Harvest time and agronomic performance of maize hybrids with contrasting growth cycles Épocas de colheita e desempenho agronômico de híbridos de milho com ciclos de crescimento contrastantes - Panison F.* (2016)
© 2016, Eduem - Editora da Universidade Estadual de Maringa. All rights reserved.The delay of the maize harvest may cause qualitative and quantitative grain losses. This work evaluated the effects of the harvest time on the agronomic performance of maize hybrids with contrasting growth cycles. The experiment was set in Lages, Santa Catarina State, South Brazil, during the 2012/2013 and 2013/2014 growing seasons. A randomized block design, arranged in split plots was used. Five single-cross hybrids were tested in the main plots: P1630H and P32R22H (hyper-early), P2530 (super early) and P30F53YH and P30R50YH (early). Five harvest times were assessed in the split plots: 0 (grain physiological maturity), 10, 20, 30 and 40 days after physiological maturity. The sowing was performed on 12/5/2012 and 10/5/2013. The percentage of lodged and broken stems, grain mass, potential and real productivity were determined. The delay of the maize harvest increased the percentage of lodged and broken stems. The harvest time did not affect the weight of 1,000 grains. The harvests performed after physiological maturity decreased the real grain productivity, especially for the hyper-early hybrids P1630H and P32R22H. In the regions with high altitude and latitude, the productivity losses derived from late harvests are mainly due to the increase in the amount of broken and lodged stems.